Teaching The Qur'an to Converts with An Islamic Education Approach: A Case Study at the Mualaf Center Yogyakarta - Rahmah, Alya; Alam, Naufal Ahmad Rijalul (ISTAWA, 2024)
Teaching the Qur'an is an essential part of Muslims in enhancing their understanding and practice of Islamic values, especially for converts who have recently embraced Islam. It serves as a fundamental foundation in deepening the teachings of Islam and building spiritual attachment. This study examines the teaching of the Qur'an for converts using an Islamic education approach. Qur'anic teaching is of great importance and needs to be conducted to form a Muslim who is fully committed to their faith and has a basic understanding of Islamic teachings. This research uses a qualitative descriptive method to gain a deep understanding of the phenomenon being studied and comprehensively explore individuals' perspectives and experiences. The research was conducted at the Mualaf Center in Yogyakarta. In this study, the researcher conducted observations and interviews with teachers and converts at the Mualaf Center Yogyakarta. Based on the research findings, it was found that the teaching of the Qur'an at the Mualaf Center Yogyakarta focuses not only on aspects of memorization and recitation of the Qur'an but also on contextual understanding and the application of Islamic educational values in everyday life. The implementation of Qur'anic teaching with an Islamic education approach at the Mualaf Center Yogyakarta is carried out through teaching Islamic educational values such as aqidah (faith), ibadah (worship), akhlak (morality), and the Qur'an, using a unique book as a guide for the converts to understand the fundamentals of Islamic teachings, routine studies every weekend, muroja'ah and Qur'an reading activities, tadabur (reflection) or the instilling of Qur'anic values by the teachers, free tattoo removal program, and social activities as part of da'wah (Islamic preaching) to instill Islamic values and so on.